Computed tomographic diagnostic evaluation of the adrenal and pituitary adenomas in Syndrome and Morbus Cushing - Shubeska Stratrova, Slavica; Jovanovska Mishevska, Sasha; Spasovski, Dejan (My University, 2020)
Cushing syndrome is the clinical manifestation of hypercortisolism. Obese subjects (O) suspected of hypercortisolism first have to be biochemically differentiated from patients with Cushing syndrome with adrenal adenoma (CS) and Morbus Cushing (MC) with pituitary adenoma and adrenal hyperplasia (AH). After the biochemical differentiation of CS and MC, computed tomographic (CT) morphological assessment is necessary by which the localization will be proved and the size of the tumor determined. The aim of this study was to determine diagnostic assessment accuracy of the CT imaging of the adrenal and pituitary adenomas in patients with CS and MC, which were biochemically, clinically and histologically, after surgery, diagnosed. Adrenal glands were assessed with CT scan in 66 subjects, 36 O suspected for Cushing’s, 14 CS and 16 MC. Pituitary CT scan was performed in 16 MC and 11 O. Sensitivity (S), specificity (SP), positive predictive value (PPV), negative predictive value (NPV) and diagnostic accuracy (DG) were determined of the CT scan test results in the examined subjects. Adrenocortical adenomas (CA) were detected by means of CT of the adrenal glands in CS as clearly determined oval, homogenous, unilateral adrenal masses with mean diameter value of 3.42±1.24 cm. CA were found in 13 of 14 CS (S 93%) and in 3 of 36 O patients (SP 91.7%), true positive results were found in 13 CS from total 16 positive (PPV 81.25%), true negative results were found in 33 O of total 34 negative (NPV 97.1%) and DG of 92% as a ratio of the sum of 13 true positive CS and 33 true negative O test results and the sum of all 50 subjects (14 CS and 36 O). In 12 of total 16 MC was found AH (S 75%), and false positive AH was found in 3 of 36 O (SP 91.7%), true positive AH results were found in 12 of total 15 positive (PPV 80%), true negative results of AH were found in 33 O from total 37 negative (NPV 89%) and DG of 86.5%. When comparing all 30 Cushing patients with 36 O, CT scan assessment showed S of 83.33%, SP 91.7%, PPV 89.3%, NPV 86.8% and DG of 87.9%. Pituitary CT scan in MC discovered pituitary microadenomas with S of 56.25%, SP 91%, PPV 90%, NPV 59% and DG of 70%. Adrenocortical adenomas in CS were detected with high S of 93%, NPV 97.1% and DG of 92% as an oval unilateral adrenal masses and discovered adrenal CT scan as a useful diagnostic procedure in adrenal tumors diagnosis. Bilateral adrenal hyperplasia in MC was determined with low S of 75% as well as PPV of 80% and DG of 86.5%. Low values of the S 56.25%, NPV 59% and DG of 70% of the pituitary CT scans as well as adrenal CT scans in MC indicated the need of previous biochemical differentiation of MC and O in order to exclude adrenal as well as pituitary incidentalomas and also showed the need of more precise MRI investigation of the pituitary gland in MC.
Keywords: cushing syndrome; CT imaging; adrenal and pituitary adenomas; diagnostic accuracy